THE INFLUENCE OF LIQUIDITY, SOLVENCY AND ACTIVITY ON RETURN ON ASSETS INCOMPANIES METALAND THE LIKE LISTED ON THE INDONESIA STOCK EXCHANGE - Hade Chandra Batubara; Ulfah Zayn (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine whether there is an influence between Liquidity (Current Ratio), Solvency (Debt to Equity Ratio and Debt to Asset Ratio) and Activity (Total Asset Turnover and Inventory Turnover) on Return on Assets, either partially or simultaneously in metal and metal companies. similar types that are listed on the Indonesia Stock Exchange from 2016 to 2020. The approach used in this study is to use an associative approach and the type of data used is quantitative. The population were 17 metal companies and the sample 8 metal companies and the like using pureposive sampling technique. Observations were carried out for 5 years starting from 2016 to 2020. The data collection technique used in this study was a documentation study. The data analysis technique in this study uses Multiple Linear Regression Analysis, Classical Assumption Test, Hypothesis Testing (t Test and F Test), and Coefficient of Determination Test. Data in this study using Software SPSS(Statistics Package for the SocialSciens)version 23. Results of this study concluded that the partial Current Ratio positive and significant effect on Return on Assets. Debt to Equity Ratio has a negative and significant effect on Return on Assets, Debt to Asset Ratio has a positive and significant effect on Return on Assets. Total Asset Turnover has no positive and insignificant effect on Return on Assets, and Inventory Turnover has no positive and insignificant effect on Return on Assets. Meanwhile, Simultaneously Current Ratio, Debt to Equity Ratio, Debt to Asset Ratio, Total Asset Turnover and Inventory Turnover have a significant effect on Return on Assets in metal and similar companies listed on the Indonesia Stock Exchange.Keywords: Current Ratio, Debt to Equity Ratio, Debt to Asset Ratio, Total Asset Turnover, Inventor Turnover and Return on Assets